Cymothoa indica Schioedte and Meinert, 1884 (Crustacea: Isopoda: Cymothoidae) infestation in cage-cultured Asian seabass Lates calcarifer (Bloch, 1790) from the south-west coast of India - Sukumaran, K.; Kailasam, M.; Jithendran, K. P. (Indian Journal of Fisheries, 2019)
Infestation of the isopod parasite Cymothoa indica  in Asian seabass Lates calcarifer (Bloch, 1790) fingerlings stocked in low volume cages is reported here. Hatchery produced seabass fry, reared to fingerling size (average size, 7±1 g and 63±12 mm) were used for stocking cages in Ashtamudi Lake, Kerala, south-west India. Instances of mortality were first observed on the 25th day of culture (DOC). By the 35th DOC, cumulative mortality of 84.6% was recorded. Intensity of parasitic infestation was found to be one parasite per fish. Parasites were observed to be latched to the tongue of the host fish. Reddening of buccal cavity, dark pigmentation, tongue degeneration/replacement were observed in the affected fish. On the 35th DOC, surviving fish in the cages were examined and the prevalence of C. indica was 53.08% in the remaining live fish. Though experimental infestation of Asian seabass by C. indica has been reported previously under laboratory conditions, this forms the first  report on infestation of C. indica in cage-cultured Asian seabass.Keywords: Asian seabass, Cymothoa indica, Cage culture,  Isopoda, Lates calcarifer